New neutron imaging techniques to close the gap to scattering applications. (January 2017) - Lehmann, Eberhard H.; Peetermans, S.; Trtik, P.; Betz, B.; Grünzweig, C.
Abstract: Neutron scattering and neutron imaging are activities at the strong neutron sources which have been developed rather independently. However, there are similarities and overlaps in the research topics to which both methods can contribute and thus useful synergies can be found. In particular, the spatial resolution of neutron imaging has improved recently, which - together with the enhancement of the efficiency in data acquisition- can be exploited to narrow the energy band and to implement more sophisticated methods like neutron grating interferometry. This paper provides a report about the current options in neutron imaging and describes how the gap to neutron scattering data can be closed in the future, e.g. by diffractive imaging, the use of polarized neutrons and the dark-field imagining of relevant materials. This overview is focused onto the interaction between neutron imaging and neutron scattering with the aim of synergy. It reflects mainly the authors' experiences at their PSI facilities without ignoring the activities at the different other labs world-wide.